Bevacizumab with preoperative chemotherapy versus preoperative chemotherapy alone for colorectal cancer liver metastases: a retrospective cohort study. Issue 35 (August 2016) - Lu, Zhen-Hai; Peng, Jian-Hong; Wang, Fu-Long; Yuan, Yun-Fei; Jiang, Wu; Li, Yu-Hong; Wu, Xiao-Jun; Chen, Gong; Ding, Pei-Rong; Li, Li-Ren; Kong, Ling-Heng; Lin, Jun-Zhong; et al.
Abstract : Abstract: This study aimed to assess the efficacy and safety of bevacizumab plus preoperative chemotherapy as first-line treatment for liver-only metastatic colorectal cancer in Chinese patients compared with those of preoperative chemotherapy alone. Patients with histologically confirmed liver-only metastatic colorectal cancer were sequentially reviewed, and received either preoperative chemotherapy plus bevacizumab (bevacizumab group, n = 32) or preoperative chemotherapy alone (chemotherapy group, n = 57). Progression-free survival, response rate, liver resection rate, conversion rate, and safety were analyzed. With median follow-up of 28.7 months, progression-free survival was 10.9 months (95% confidence interval: 8.7–13.1 months) in bevacizumab group and 9.9 months (95% confidence interval: 6.8–13.1 months) in chemotherapy group ( P = 0.472). Response rates were 59.4% in bevacizumab group and 38.6% in chemotherapy group ( P = 0.059). Overall liver resection (R0, R1, and R2) rate was 68.8% in bevacizumab group and 54.4% in chemotherapy group ( P = 0.185). Conversion rate was 51.9% in bevacizumab group and 40.4% in chemotherapy group ( P = 0.341). No postoperative complication was observed in all patients. Bevacizumab plus preoperative chemotherapy as first-line treatment for liver-only metastatic colorectal cancer tends to achieve better clinical benefit with controllable safety in Chinese patients.